Radiation from a millimeter-wave rectangular waveguide slot array antenna enclosed by a Von Karman radome - Kim, Jihyung; Song, Sung Chan; Shin, Hokeun; Park, Yong Bae (Journal of Electromagnetic Engineering and Science, 2018)
In this paper, electromagnetic radiation from a slot array antenna enclosed by a Von Karman radome is analyzed by using the ray tracing method and Huygens's principle. We consider the rectangular slot array antenna and the Von Karman radome. The radiation patterns are calculated by using the surface currents of the radome to illustrate the electromagnetic behaviors of the radome-enclosed waveguide slot array antenna.
Keywords: Ray tracing technique; Slot array antenna; Von Karman radome